Banking and agriculture in Peru before the war with Chile, 1866-1879 - De la Torre Zevallos, Marco Antonio (2021)
The objective of this article is to showcase the importance of the Banco de Crédito Hipotecario in the resurgence of export agriculture in Peru before the war with Chile. This bank is considered the first to be created to finance productive activities, such as export agriculture, in unproductive times when the Peruvian economy depended and revolved around guano exports. The article also seeks to demonstrate that the mercantile and banking bourgeoisie, criticized for being simple rentiers who lived at the expense of the Peruvian State invested their capital in financial institutions, such as the Banco de Crédito Hipotecario, to finance the development of the country through productive activities such as export agriculture that could generate income and avoid fiscal dependency on guano exports.